2004
DOI: 10.1074/jbc.m309063200
|View full text |Cite
|
Sign up to set email alerts
|

Akt Is a Neutral Amplifier for Th Cell Differentiation

Abstract: Both CD28 and its relative, inducible costimulator (ICOS), have a binding motif for phosphatidylinositol 3-kinase (PI3K) in their cytoplasmic tail, and the binding of PI3K leads to activation of a serine/threonine kinase, Akt. The role of Akt in cytokine production and helper T (Th) cell differentiation remains obscure. In this study, we found that enforced expression of the constitutively active form (E40K) of Akt rendered CD4 ؉ T cells activated. Wild-type of Akt and E40K promoted Th1 cell differentiation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 60 publications
2
24
0
Order By: Relevance
“…A number of PIP3-dependent kinases have also been implicated in the regulation of Th1 and Th2 differentiation: Itk and Pdk1 were reported to be required for Th2 differentiation (17,35), whereas Akt has been shown to promote both Th1 and Th2 differentiation (36,37). Our results are most consistent with PI3K signaling being required for both Th1 and Th2 differentiation, without preferential skewing toward either differentiation pathway.…”
Section: Discussionsupporting
confidence: 80%
“…A number of PIP3-dependent kinases have also been implicated in the regulation of Th1 and Th2 differentiation: Itk and Pdk1 were reported to be required for Th2 differentiation (17,35), whereas Akt has been shown to promote both Th1 and Th2 differentiation (36,37). Our results are most consistent with PI3K signaling being required for both Th1 and Th2 differentiation, without preferential skewing toward either differentiation pathway.…”
Section: Discussionsupporting
confidence: 80%
“…Suzuki et al (42) showed that mice lacking PTEN, which is a phosphatase for PIP3, exhibit enhancement of PI3K signal pathway and increase in both Th1 and Th2 cytokine production. Arimura et al (43) demonstrated that overexpression of Akt, a major downstream target of PI3K, resulted in amplification of both Th1 and Th2 development. Furthermore, Schaeffer et al (44) have reported that Tec family tyrosine kinase Itk, which is also regulated by PI3K, has an important role for Th2 development.…”
Section: Cd4mentioning
confidence: 99%
“…31,32 We observed a profound defect in the capacity of CD4 ϩ CD25 ϩ Treg cells to activate AKT upon stimulation via CD3 and CD28 and, after 10 minutes, the increase in levels of phospho-AKT (Ser473) was only 1.8-fold Ϯ 0.17-fold in CD4 ϩ CD25 ϩ Treg cells compared with 3.2-fold Ϯ 0.58-fold in CD4 ϩ CD25 Ϫ T cells (P Ͻ .001, n ϭ 11; Figure 2A). Analysis more than 30 minutes following stimulation revealed that the reduction in phosphorylation of Ser473 was not due to altered kinetics of activation.…”
Section: Human Cd4 ؉ Cd25 ؉ Treg Cells Have a Reduced Capacity To Phomentioning
confidence: 99%